2018
DOI: 10.3390/ijms19092511
|View full text |Cite
|
Sign up to set email alerts
|

The Promise of Novel Biomarkers for Head and Neck Cancer from an Imaging Perspective

Abstract: It is an agreed fact that overall survival among head and neck cancer patients has increased over the last decade. Several factors however, are still held responsible for treatment failure requiring more in-depth evaluation. Among these, hypoxia and proliferation-specific parameters are the main culprits, along with the more recently researched cancer stem cells. This paper aims to present the latest developments in the field of biomarkers for hypoxia, stemness and tumour proliferation, from an imaging perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…Next to radiomic signatures, there is a myriad of other prognostic biomarkers for HNSCC available that, for instance, are based on imaging [41], immunohistochemistry [42], and microarray data [4]. The advantages of our radiomic profile is that it is available before treatment and based on standard diagnostic images, thereby avoiding additional costs and discomfort for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Next to radiomic signatures, there is a myriad of other prognostic biomarkers for HNSCC available that, for instance, are based on imaging [41], immunohistochemistry [42], and microarray data [4]. The advantages of our radiomic profile is that it is available before treatment and based on standard diagnostic images, thereby avoiding additional costs and discomfort for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical management of tumour heterogeneity is a significant challenge as tumour response is dictated by the particular behaviour of each sub-group of cancer cells. Cellular heterogeneity given by proliferation kinetics, stemness, hypoxia or other factors calls for specific markers and targeting; therefore, the near future of biomarkers will rely on complementarity rather than a common solution valid for all (radio)biological particularities of a tumour [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the possibility of the coexistence of false-positive findings owing to thyroid lesions must be considered and further evaluation is required when another focal lesion is seen on a Tc-99m MIBI SPECT scan [21,22]. Furthermore, similar to this MIBI SPECT/CT, a recent study reported the importance of hybrid imaging using tumor-specific biomarkers in head and neck tumors, and this is thought to help the patients’ treatment guidance [23].…”
Section: Discussionmentioning
confidence: 99%